The Content and Methods of Shaping Creativeness in the Preparation of Bakalevr towards Technological Instruction - Khasanboevna, Zhaloldinova Shakhnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
Pedagogical communication is understood by the content, methods and skills of teacher and audience about the content of the border movement between the team of mutual action between the team of mutual movement.